(untitled) (Human Factors in Design, 2022)
Design might be a means to promote accessibility and inclusion in healthcare sector. This study aims to identify relationships between the concepts of inclusive design (ID) and user-centered design (UCD) with accessibility and inclusion in the context of health innovation. As a methodology, a systematic literature review was made. The papers that presented intersections between ID and UCD were categorized into: user-centeredness concurrent with inclusion; and with greater user involvement. It was found that this involvement does not occur from the outset in design solutions in many of the studies. The innovations proposed by all articles are configured as incremental.